The oxidoreductase p66Shc acts as tumor suppressor in BRAFV600E‐transformed cells - Tobias Furlan; Sana Khalid; Anh‐Vu Nguyen; Julia Günther; Jakob Troppmair (Molecular Oncology, 2018)
Metabolic reprogramming, as exemplified by the shift from oxidative phosphorylation to glycolysis, is a common feature of transformed cells. In many tumors, altered metabolism is also reflected in increased reactive oxygen species (ROS) levels, which contribute to proliferation and survival signaling. However, despite high ROS levels, cancer cells can be efficiently killed by further increasing ROS production. We have shown previously that both wild‐type and oncogenic CRAF and BRAF prevent excessive mitochondrial ROS production. Subsequently, it has been demonstrated that raising ROS levels in BRAFV600E‐transformed melanoma cells by inhibiting BRAF or MEK rendered them susceptible to cell death induction. To understand how oncogenic BRAF affects mitochondrial ROS production in melanoma, we studied the mitochondrial ROS‐producing oxidoreductase p66Shc, which is frequently overexpressed in tumors. Using NIH 3T3 BRAFV600E fibroblasts and the melanoma cell lines A375 and M238 carrying the same BRAF mutation, we show that under treatment with the ROS‐inducing agent phenethyl isothiocyanate (PEITC), oncogenic BRAF renders cells refractory to p66ShcS36 phosphorylation, which is essential for p66Shc activation and mitochondrial ROS production. Consistent with this, the activation of JNK1/2, which phosphorylate S36, was blunted, while other mitogen‐activated protein kinases were not affected. Inhibition of JNK1/2 efficiently prevented ROS production, while BRAF and MEK inhibitors increased ROS levels. Vemurafenib‐resistant M238R melanoma cells were impaired in S36 phosphorylation and ROS production following PEITC treatment. Moreover, they failed to increase ROS levels after MEK/BRAF inhibition. Finally, shRNA‐mediated knockdown of p66Shc led to increased growth of BRAFV600E‐transformed NIH 3T3 cells in soft agar assay. Taken together, these data suggest that phosphorylation‐activated p66Shc functions as a tumor suppressor in melanoma cells.